DEVELOPING A MODEL, CRITERIA, AND ASSESSMENT FRAMEWORK FOR FOSTERING DIGITAL REFLECTION IN HIGHER EDUCATION UNDER CONDITIONS OF DIGITAL TRANSFORMATION - Muxayyo Shakirovna Salixova (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
In the context of contemporary globalization and digital transformation, the higher education system is undergoing a phase of profound modernization. The rapid development of information and communication technologies, the integration of artificial intelligence systems into the educational process, and the expansion of electronic learning environments are prompting a reconsideration of traditional teaching models. Consequently, this necessitates the revision of the content, forms, and assessment mechanisms of the educational process. In particular, the development of students’ competencies in independent learning, critical thinking, self-regulation, and reflective practice has become one of the key priorities of modern pedagogy.